Jejak Pemikiran Abdullah Ahmad dalam Perkembangan Pendidikan Islam di Sumatra Barat - Nadifa Sabrina; Faiq Alfath; Ilyas Habiburrohman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the evolution of Islamic education in Minangkabau and its relationship with the development of knowledge within society. Islamic education in Minangkabau has experienced significant transformations, beginning with the traditional surau system, developing into madrasahs, and eventually evolving into modern Islamic schools. These changes reflect the community’s efforts to adapt educational practices to social, cultural, and intellectual developments while preserving Islamic values. This research employs a qualitative method with a historical approach, utilizing documents, archives, and relevant literature as primary sources of data. Through an analysis of historical records, the study identifies three major phases in the development of Islamic education in Minangkabau: the traditional phase represented by surau institutions, the transitional phase marked by the emergence of madrasahs, and the modern phase characterized by integrated Islamic schools. The findings indicate that Islamic reformers played a crucial role in encouraging the integration of religious and general education. This integration contributed to curriculum improvement, educational innovation, and broader access to learning opportunities for the community. Overall, the history of Islamic education in Minangkabau demonstrates dynamic changes in social, cultural, and intellectual dimensions, leading to the establishment of a more comprehensive, adaptive, and sustainable educational system.